Badanie efektywności zmodyfikowanych metod aglomeracyjnych na zbiorach danych ze świata realnego - Korzeniewski, Jerzy (Investigating the Efficiency of Modified Agglomerative Methods on Real World Data Sets, 2008)
In the paper, the efficiency of agglomerative clustering algorithms is investigated with a special focus on the author's own modifications. The following clustering algorithms are examined: single link, complete link, group average link and centroid link. The idea of the modifications is to stress the local distribution of observations together with clustering based on the dissimilarity matrix. The quality of clustering is assessed by means of the silhouette indices. The results prove that the author's modifications almost always improve the standard methods.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 462-469